The Psychometric Characteristics of the Exercise Benefits/Barriers Scale among Iranian Elderly. - Ahmad Ali Akbari Kamrani; Seyed Hojjat Zamani Sani; Zahra Fathire-Zaie; Mahdi Bashiri; Ebrahim Ahmadi (Tehran University of Medical Sciences, 2014)
The objective of this study was to investigate the validity and reliability of the Farsi version of the perceived benefits/barriers scale of physical activity in Iranian elderly.Overall, 388 elderly subjects (60 yr and over) completed the demographic characteristics questionnaire, the Exercise Benefits/Barriers Scale (EBBS) and the Yale physical activity scale. Data were analyzed through of exploratory factor analysis, using Varimax rotation, Cronbach's alpha and Pearson correlation.The matrix table of rotated elements of Farsi version of EBBS showed ten components, and 41 items predicted 61.83% of variance. 28 items in 5 components for benefits of, and 13 items in 5 components for barriers to physical activity were identified. Cronbach's alpha for internal consistency in the whole scale and its subscales was 0.83, 0.94 and 0.68. In addition, positive and significant correlation was found between overall benefits and their sub-scales as well as between overall barriers and their subscales. Moreover, there was significant and positive correlation between physical activity and the benefits (r=0.209, P=0.005) and significant negative correlation between physical activity and the barriers (r=-0.231, P=0.001).The results showed acceptable reliability and validity of the Farsi version of Exercise Benefits/Barriers Scale among Iranian elderly.